2017
DOI: 10.1002/jcb.26155
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin D3 Alters the Expression of Toll‐like Receptors in Peripheral Blood Mononuclear Cells of Patients With Systemic Lupus Erythematosus

Abstract: Systemic lupus erythematosus (SLE) is an autoimmune disease characterized by production of inflammatory cytokines and autoreactive antibodies due to the loss of immune tolerance. Recognition of self-nucleic acids by intracellular Toll-like receptors (TLRs) can overactivate immune responses and this abnormal activation of TLRs contributes to the pathogenesis of the disease. In recent years, anti-inflammatory and immunomodulatory effects of 1,25-dihydroxyvitamin D3 (VitD3) on the immune system has received parti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
26
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

6
2

Authors

Journals

citations
Cited by 27 publications
(28 citation statements)
references
References 28 publications
2
26
0
Order By: Relevance
“…Systemic lupus erythematosus is a potentially severe autoimmune disease with characteristic production of inflammatory cytokines and autoreactive antibodies due to the lack of immune tolerance leading to diverse clinical manifestations and damage to various organs, including skin, joints, kidneys, and the central nervous system [13]. SLE course is variable, mainly characterized by remission and relapse periods [14].…”
Section: Discussionmentioning
confidence: 99%
“…Systemic lupus erythematosus is a potentially severe autoimmune disease with characteristic production of inflammatory cytokines and autoreactive antibodies due to the lack of immune tolerance leading to diverse clinical manifestations and damage to various organs, including skin, joints, kidneys, and the central nervous system [13]. SLE course is variable, mainly characterized by remission and relapse periods [14].…”
Section: Discussionmentioning
confidence: 99%
“…Increased levels of antinuclear antibodies, IL-23, and IL-17 (important for Th17 development and function) were also significantly associated ( p < 0.05) with a vitamin D deficiency ( 120 ). Abnormal activation of toll-like receptors (TLRs) contributes to the pathogenesis of SLE, and, interestingly, vitamin D exerts some of its immunomodulatory effects in patients with SLE by significantly downregulating the expression levels of TLR3 ( p = 0.03), TLR7 ( p = 0.0001), and TLR9 ( p = 0.007) ( 150 ). Autoimmune diseases like SLE may result from a conversion of Treg cells into Th17 cells, and in the serum of patients with SLE, IL-17 levels were abnormally high.…”
Section: Micronutrientsmentioning
confidence: 99%
“…The stimulation by TLR was said to have a mechanistical effect on innate immunity that could increase differentiation of the Th1 cell, maintain an anti-inflammatory state, and induce modulatory cytokine such as IL-10 and TGF-β, along with an increased level of intestinal IgA (Gourbeyre, Denery, & Bodinier, 2011;Marschan et al, 2008). Many studies showed that probiotics promote the stimulation of uptake receptors on blood polymorphonuclear leukocytes, and can induce higher expression of TLRs and complement receptor 3 (CR3), which are involved in a phagocytic capacity (Fang, Elina, Heikki, & Seppo, 2000;Niers et al, 2005;Pagnini et al, 2010;Yazdanpanah et al, 2017). The lactobacilli strain in different doses showed that it can enhance or suppress T cell immune responses (Wen et al, 2012).…”
Section: The Mechanism Of Immunoregulators or Immunostimulatory Promentioning
confidence: 99%